Management strategy for sustainable technology creation and accuracy in adoption: R&D perspective - V.G. Dhanakumar (Journal of Agricultural Extension Management, 2025)
If an R&D unit is in the process of generating a technology, its success (o.:-) failure may determine the future of the unit based on the pertinence and. applicability of technology. Therefore, a need for developing highly accurate Technology and its sustainability to certain location (or) group is essential. The accuracy criterion should be considered in a relative sense: how accurate must the technology be for the specific location (or) crisis management? In brief, technology accuracy for agri-commodity business (ACB) sector must be assessed relative to the importance of the adoption, the adaptation and consequences of non-adoption. Even if technology possesses all the characteristics, it is of no use unless it is relevant to current market and crisis situation. The issue of accuracy is important for those planning for, or crisis management activities to build sustainability within the system